Leptosphaeria maculans AvrLm9: a new player in the game of hide and seek with AvrLm4‐7. (1st March 2018) - Ghanbarnia, Kaveh; Ma, Lisong; Larkan, Nicholas J.; Haddadi, Parham; Fernando, Wannakuwattewaduge Gerard Dilantha; Borhan, Mohammad Hossein
Summary: Blackleg disease of Brassica napus caused by Leptosphaeria maculans ( Lm ) is largely controlled by the deployment of race‐specific resistance ( R ) genes. However, selection pressure exerted by R genes causes Lm to adapt and give rise to new virulent strains through mutation and deletion of effector genes. Therefore, a knowledge of effector gene function is necessary for the effective management of the disease. Here, we report the cloning of Lm effector AvrLm9 which is recognized by the resistance gene Rlm9 in B. napus cultivar Goéland. AvrLm9 was mapped to scaffold 7 of the Lm genome, co‐segregating with the previously reported AvrLm5 (previously known as AvrLmJ1 ). Comparison of AvrLm5 alleles amongst the 37 re‐sequenced Lm isolates and transgenic complementation identified a single point mutation correlating with the AvrLm9 phenotype. Therefore, we renamed this gene as AvrLm5‐9 to reflect the dual specificity of this locus. Avrlm5‐9 transgenic isolates were avirulent when inoculated on the B. napus cultivar Goéland. The expression of AvrLm5‐9 during infection was monitored by RNA sequencing. The recognition of AvrLm5‐9 by Rlm9 is masked in the presence of AvrLm4‐7, another Lm effector. AvrLm5‐9 and AvrLm4‐7 do not interact, and AvrLm5‐9 is expressed in the presence of AvrLm4‐7. AvrLm5‐9 is the second Lm effector for which host recognition is masked by AvrLm4‐7. An understanding of this complex interaction will provide new opportunities for the engineering of broad‐spectrum recognition.